الدرس الكلامي والتكامل المعرفي مع الفقه والتصوف - رحومة محمد العربي (University Of Eloued جامعة الوادي, 2024)
مما يؤسف له في زماننا هذا, أن عددا من الباحثين في حقل العلوم الإسلامية أحاطوا مجال اشتغالهم بأسوار عازلة تمنعهم من الاطلاع على مختلف التخصصات العلمية الأخرى، ومن شأن هذه الرؤية الضيقة أن تحجب عنه تمام الصورة العلمية وحقيقتها. إن المدقق في الإنتاج العلمي لصوفية الغرب الإسلامي، يجده كثيرا في عدده، شموليا في مادته وتناوله، نوعيّاً في منهجه ومقاربته؛ فقد تعمق شيوخُه في كل العلوم الشرعية، وشاركوا في جل المعارف الإنسانية، فكان منهم الأصولي، والفقيه، والصوفي، مع حيازة كثير منهم قصبَ السبق في علم التوحيد. لقد أدرك صوفية الغرب الإسلامي، وعلى رأسهم الإمامُ زَروق، ذلك الترابط القوي بين العقيدة والفقه والتصوف، باعتبار هذه العلوم الثلاثةِ ممثِّلةً للأصول المذكورة في حديث جبريل عليه السلام المعروف، فتبين لهم أن التوفيق بينها من آكد ما تجب العناية به، فاختار جلهم منهج الإمام أبي الحسن الأشعري في العقيدة، ومذهبَ الإمام مالك في الفقه، ومسلكَ الإمام الجنيدِ في التصوف. ومنه فإنه لا يمكن أن نؤسس درسا كلاميا إلا في ضوء التكامل المعرفي بينه وبين العلوم الأخرى واستثمار الخبرات الفقهية والصوفية Abstract: Unfortunately speaking for a number of researchers in the field of Islamic sciences that have fixed on their field of work in isolation of seeing the various other scientific disciplines which would narrow the complete scientific picture and its truth. The accurate researcher of the scientific production of the Sufism of the Islamic West finds it large in its number, comprehensive in its material and approach, and qualitative in its methedology and approach furthermore their scholars discussed deeply all the religious sciences, and participated in most of the human knowledge. Among them were the fundamentalists the jurist, and the soufis over welmanig majer of them making the priority of the science of monotheism. The Sufis of the Islamic West, led by Imam Zaruq, realized the strong interdependence between belief, jurisprudence, and Sufism, considering these three sciences as representative of the principles mentioned in the well-known hadith of Jibril, peace be upon him. Al-Hassan Al-Ash'ari in the creed, the doctrine of Imam Malik in jurisprudence, and the path of Imam Al-Junaid in Sufism. Hence, it is not possible to establish a verbal lesson except in light of the cognitive integration between it and other sciences and the investment of jurisprudential and Sufi experiences in building the verbal lesson because the goal is to build the human being of the caliphate (body, spirit, mind, values and perceptions)..
زروق الفاسي أنموذجا
أطروحة
Keywords: الدرس الكلامي; التكامل المعرفي; الفقه; التصوف; Theological lesson; cognitive integration; jurisprudence; Sufism